Teachers' practices in handling children with parent-child attachment problems : a case study in a selected pre-school in Selangor - Hartini Mat Hussain (Kulliyyah of Education, International Islamic University Malaysia, 2019)
The case study was conducted in a private pre-school in Selangor explore the pre-school teachers' practices and the challenges in handling children with attachment problems more specifically with the parents as well as the characteristics that the children exhibit during the trial class. The participants' views were explored in relation to the teachers' practices and challenges they faced with the children involved. This study investigated what teachers' thoughts of practices that they believe to be effective and the barriers and challenges to the children's positive acceptance and behaviours to pre-school enrolment. Findings were extracted from interviews from 3 pre-school teachers from one pre-school. The participants have more than two years experience handling children with parent-child attachment problems both during orientation week and trial class. Three themes were gathered from the data collected. Parents' cooperation is the first theme found in this study that resulted to the positive relationship between teachers and parents led to facilitating the children's preparedness in school. The second theme was teachers' preparation that resulted in positive and smooth process during trial class. The last theme configured in this study is the teachers' affection that led to positive behaviours and trust building in children during the trial class. This theme is in relevance to several previous literature provide extensive findings to young children that helps in children's acceptance to new environment. Meanwhile, teachers' challenges were broken down to two themes. The first theme is the absence of parents' preparation which resulted to children's less preparedness in meeting new environment. The second theme is parents' cooperation during the trial class which led to negative behaviours in the children during the trial class. The findings that are related to extant literature on children's attachment problems, provide evidence that parents' cooperation and preparation would be beneficial for positive behaviours in children entering pre-school.